Investigações acerca da abordagem do tema meio ambiente e do desenvolvimento de ações interdisciplinares no ensino fundamental - Viçosa, Cátia Silene Carrazoni Lopes (2017)
Scientific studies indicate that discussions and proposals related to the theme of Environment, interdisciplinarity and continuing teacher education have long come from Brazilian publications. These proposals have the prospect of contributing to a better quality of teaching and to the basis of educational actions. In this context, the present study had as objective to investigate the orientations and strategies adopted by teachers of the final years of Elementary Education on the Environment and Interdisciplinarity. The methodological approach is based on the qualitative-quantitative analysis and was developed with teachers from the final years of elementary school in a school in the city of Uruguaiana/RS. It covered a documentary analysis of the School's Political Pedagogical Project, through an analytical matrix, aiming to identify the content of its orientations and used a semistructured questionnaire to characterize the researched group, delineating data regarding initial and continued formation, teaching time and load. It also aimed to identify their perceptions and pedagogical practice regarding the Environment and Interdisciplinarity, and how continuing education contributes to the development of these issues. The results showed that the Political Pedagogical School Project is outdated and does not contemplate concrete proposals, referring to the Environment, interdisciplinarity and the continued formation of teachers. It was found that most teachers do not know the document that governs the school; do not develop activities on the Environment and do not use interdisciplinarity as strategies to develop their educational actions. We also identified a deficit in relation to effective continuing education, which covers the themes discussed here in the different training areas. It was concluded that, in order to remedy the gaps, analyzed here, it is essential to reformulate the school project, contemplating aspects relevant to the school context, such as democratic management, interdisciplinarity, Environment and other Transversal Themes, with the participation of all segments. It is also imperative to invest in proposals for ongoing training, with the intention of meeting the needs of the lagged initial training, instrumentalizing and enabling a professional improvement in relation to the Environment and interdisciplinarity, resulting in concrete educational actions that contribute to the teaching and learning process learning. It is inferred, therefore, that the constituent elements and constituents of the continuous formation, in the perspective pointed out in this dissertation, are configured as humanization-social development enhancers and contribute to overcoming ruptures between sense and meaning of this formation. It is hoped that the data presented in this research can contribute to further studies on Political-Pedagogical Projects, Environment and interdisciplinarity in the school context, generating reflections and problematizations for the development of the quality of teaching in our country.